On the relevance of values, norms, and economic preferences for electricity consumption - Elke D. Groh; Andreas Ziegler (Philipps-University Marburg, School of Business and Economics, 2021)
Based on data of more than 3700 citizens in Germany, this paper empirically examines the relevance of several groups of explanatory factors for electricity consumption. Besides controlling for individual housing and dwelling characteristics as well as socio-demographics, we analyze the effect of environmentally-related values and norms. Since behavioral economics reveals the importance of economic preferences for many individual activities, we additionally consider time and risk preferences, altruism, trust, and reciprocity in our econometric analysis. With respect to the latter factors, only patience has a significantly negative effect on electricity consumption. Our estimation results instead suggest a high relevance of individual housing and dwelling characteristics and socio-demographics. The most interesting result is probably that neither environmentally-related values such as ecological policy identification and environmental awareness nor environmentally-related social norms have a significant effect. In contrast to the USA and to the demand for green electricity in Germany, these estimation results suggest that citizens in Germany with strong environmental identity do not consider low electricity consumption as an important direction for environmental and climate protection.
Keywords: 330; Electricity consumption; values; norms; economic preferences; econometric analysis